Internalization of Islamic Values in Education with Strategic and Applicative Studies at MA Al-Quraniyah Manna - Rendi, Rendi; Nurlaili, Nurlaili (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to explore strategies for internalizing Islamic values in character building at MA Al-Quraniyah Manna. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The findings show that value-based learning, habituation, and religious extracurriculars are effectively implemented with strong support from school leaders and teachers through modeling and educational discipline. The strategy successfully fosters students' moral character, independence, and social spirit. The study concludes that collaboration with families and communities is essential, and value-based programs should adapt to current societal changes.